Władysław Bartynowski – numizmatyk i jego rodzina - Pawłowska, Krystyna (2025)
This book is devoted to the Bartynowski family of Kraków. Although presented in the form of a family narrative, it is firmly grounded in sources and documents that the author – herself a member of the famil y– gathered primarily from private family collections and archives. The central figure of the story is Władysław Bartynowski (1832–1918), a renowned numismatist, print collector, bibliophile, antiquarian, publisher of facsimiles of early printed books, book conservator, creator of bartynotypia (a technique for reproducing coins), co-founder of the Polish Numismatic Society, editor of the journal “Wiadomości Numizmatyczno-Archeologiczne”, curator of Count Andrzej Potocki’s collections, benefactor of museums, and a patriot. Nearly half the book is dedicated to his life and work.
Keywords: numismatics; collecting; bookselling; prints; bartynotypie; Kraków heritage; patriotism